2019
DOI: 10.1080/1331677x.2019.1638288
|View full text |Cite
|
Sign up to set email alerts
|

A Preference for Corporate Borrowing in Alternative Markets over Borrowing from Banks under the Impact of Monetary Policies: a Lithuanian Case

Abstract: An analysis of the scientific literature has revealed that companies in advanced countries have mixed capital structures, whereas companies in less advanced countries mostly depend on bank credits and loans. The reason for dependence on bank funding lies in the fact that corporate bonds are profitable only to large companies with a high credit rating, while small and medium companies-as well as large companies with lower credit ratings-find bank loans to be a more attractive method of external financing. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The academic research on the country-level determinants presents the main division into government and corporate bonds, and the studies on the firm-level determinants produce the split into domestic and international corporate bond issuance. The study of Gaspareniene et al (2019) further divided the determinants into general economic determinants, bank sector determinants, money market determinants, and specific characteristics of a company.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The academic research on the country-level determinants presents the main division into government and corporate bonds, and the studies on the firm-level determinants produce the split into domestic and international corporate bond issuance. The study of Gaspareniene et al (2019) further divided the determinants into general economic determinants, bank sector determinants, money market determinants, and specific characteristics of a company.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lithuanian corporate bond market is either studied in a bigger sample of countries for government debt issuance or in the context of alternative to bank-base borrowing. Gaspareniene et al (2019) identified the link between corporate borrowing in the financial markets and bank requirements for borrowers based on the strict legal regulation of the banking sector. Levisauskaite et al (2014) included both Latvia and Lithuania in their analysis of the link between the stock market and sovereign bond markets in the European Union (EU) countries, while one of the conclusions indicated that the Lithuanian market distinguished from other European countries as assumed by the authors, potentially caused by lack of data, different indi-ces used or the country being among new members of the European Union.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies in developed countries have mixed capital structures, while companies in less developed countries are largely dependent on bank loans and credits. Interest rates and bond yields exercise important effect on company's borrowing decision (Gaspareniene et al, 2019;Redo, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%